Penerapan Metode Role Playing untuk Meningkatkan Keterampilan Berbicara Pada Siswa Kelas IV SD Negeri Pengalasan - Puguh Cahyo Santoso; Sukadari Sukadari (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to (1) describe the steps for implementing the role playing method to improve speaking skills (role playing) in fourth grade students of SD Negeri Pengalasan; (2) describe the improvement of speaking skills in learning to play a role in the fourth grade students of SD Negeri Pengalasan using the role playing method; and (3) describe the responses of fourth graders at the Pengalasan Elementary School to the application of the role playing method in an effort to improve speaking skills in learning to speak. This study uses a classroom action research design (CAR). The subjects of this study were teachers and fourth grade students of Pengalasan Elementary School. The data collection method used is the observation method, the test method, the questionnaire method, and the interview method. Data were analyzed using qualitative descriptive techniques and quantitative descriptive analysis techniques. The results showed that, (1) the appropriate learning steps in this study were emphasized on three things, namely affirming the way of expression, updating learning media that occurred close to students' lives, and randomizing the order of groups and providing opportunities for students to determine their own roles; (2) the application of the role playing method can improve speaking skills (role playing). In the pre-action classical average score of 65 (adequate), the first cycle obtained a classical average score of 74.5 (good), while in the second cycle the classical average score was 80.5 (good); (3) students gave a very positive response to learning to speak (role playing) through the application of the role playing method. Therefore, it is hoped that teachers can apply this model.